2019
DOI: 10.1002/ejoc.201900726
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Functionalized Acylsilanes by Diol Cleavage of Cyclic 1,2‐Dihydroxysilanes

Abstract: We report a study on diol cleavage of cyclic 1,2‐dihydroxysilanes for the preparation of functionalized acylsilanes. Sodium periodate turned out to be an efficient reagent for this transformation, resulting in good to excellent yields. The method is characterized by mild reaction conditions, and sometimes simple aqueous workup of the reaction mixture was sufficient to obtain the acylsilanes in high purity. An acyclic 1,2‐dihydroxysilane was readily cleaved as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In 2019, Metz's group described another approach to synthesize bifunctional acylsilanes via diol cleavage of cyclic 1,2‐dihydroxysilanes (Scheme ) . In this work, the target bifunctional acylsilanes was obtained in excellent yields by using NaIO 4 as the oxidant.…”
Section: The Synthesis Of Acylsilanesmentioning
confidence: 99%
“…In 2019, Metz's group described another approach to synthesize bifunctional acylsilanes via diol cleavage of cyclic 1,2‐dihydroxysilanes (Scheme ) . In this work, the target bifunctional acylsilanes was obtained in excellent yields by using NaIO 4 as the oxidant.…”
Section: The Synthesis Of Acylsilanesmentioning
confidence: 99%
“…7 In 2015 Fu et al reported the preparation of enol derivatives employing the Shapiro reaction. Acetophenone (23) as well as cyclopentanone (27a) and cyclohexanone (27b) reacted with 2,4,6-triisopropylbenzenesulfonyl hydrazide (TPSH) and formed trisyl hydrazone derivatives 24, 28a and 28b in 63, 68 and 68% yields, respectively. Further treatment with n-BuLi in the presence of bicyclo[4.2.0]octa-1,3,5-trien-7-one (25) produced alcohols 26, 29a and 29b in 70, 47 and 50% yields, respectively.…”
Section: Shapiro and Bamford-stevens Reactions -Achievements In Recen...mentioning
confidence: 99%
“…Further treatment of compounds 64a,b with n-BuLi in the presence of TMEDA and TMSCl led to the formation of vinylsilanes 65a-b, in 48 and 66% yield, respectively. 23 Maier et al investigated the transfer hydrogenation protocol for imines, olefins as well as N-heteroarenes using cobalt complexes. Thus, a structurally challenging, polycyclic olefin was synthesized according to the Shapiro reaction protocol.…”
Section: Shapiro and Bamford-stevens Reactions -Achievements In Recen...mentioning
confidence: 99%